Activation of the TGF-β1/Smad signaling by KIF2C contributes to the malignant phenotype of thyroid carcinoma cells. (December 2021) - Lin, Qiuyu; Qi, Qianle; Hou, Sen; Chen, Zhen; Jiang, Nan; Zhang, Laney; Lin, Chenghe
Highlights: KIF2C is upregulated in thyroid carcinoma. KIF2C promotes the proliferation and metastasis of thyroid carcinoma cells. KIF2C regulates the activation of TGF-β1/Smad signaling. KIF2C promotes thyroid carcinoma cell proliferation via the TGF-β1/Smad signaling. KIF2C promotes thyroid carcinoma cell metastasis via the TGF-β1/Smad signaling. Abstract: Kinesin family member 2C (KIF2C) has been identified as a potential oncogene in various types of human cancers; however, the role of KIF2C in thyroid cancer has not yet been elucidated. Quantitative real-time polymerase chain reaction and western blotting were employed for gene expression analysis. Cell Counting Kit-8 and ethynyl-2′-deoxyuridine assays were performed to examine cell proliferation. Cell migration and invasion were assessed by wound-healing and transwell invasion assays. Results showed that KIF2C expression was upregulated in thyroid carcinoma cell lines. In addition, upregulation of KIF2C promoted the proliferation, migration, and invasion of thyroid carcinoma cells, while downregulation of KIF2C exerted the opposite effects. Overexpression of KIF2C induced the activation of transforming growth factor-β1 (TGF-β1)/Smad signaling in thyroid carcinoma cells. However, inhibition of TGF-β1/Smad signaling through silencing TGF-β1 attenuated the promoting effects of KIF2C overexpression on the malignant phenotype of thyroid carcinoma cells. Besides, overexpression of TGF-β1 suppressed the inhibitory effect of KIF2C knockdown on the proliferation and metastasis of thyroid carcinoma cells. In conclusion, our findings demonstrated that KIF2C contributed to the malignant phenotype of thyroid carcinoma cells by inducing the activation of TGF-β1/Smad signaling, thus uncovering a novel mechanism for thyroid carcinoma progression.